2022
DOI: 10.1096/fj.202200132r
|View full text |Cite
|
Sign up to set email alerts
|

AREG is involved in scleral remodeling in form‐deprivation myopia via the ERK1/2‐MMP‐2 pathway

Abstract: Previous studies have found that amphiregulin (AREG) may participate in eye elongation during the development of myopia, but the mechanism remains unclear. Here, we tested tear concentrations of AREG in adults and detected the role of AREG in scleral remodeling in form‐deprivation myopia (FDM) in guinea pigs. We found the tear concentrations of AREG in myopes were significantly higher than those in emmetropes using enzyme‐linked immunosorbent assay (ELISA). Tear concentrations of AREG were negatively correlate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2
2

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 41 publications
0
4
0
Order By: Relevance
“…In mice overexpressing adcy1, the levels of p-ERK in the forebrain are elevated above normal [ 48 ]. Elevated expression of p-ERK aggravates scleral remodeling in myopia [ 49 ]. Because adcy1 activity can be dynamically regulated by calcium and neuronal stimulation, adcy1 function is related to the regulation of neuronal signal transduction [ 50 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In mice overexpressing adcy1, the levels of p-ERK in the forebrain are elevated above normal [ 48 ]. Elevated expression of p-ERK aggravates scleral remodeling in myopia [ 49 ]. Because adcy1 activity can be dynamically regulated by calcium and neuronal stimulation, adcy1 function is related to the regulation of neuronal signal transduction [ 50 ].…”
Section: Discussionmentioning
confidence: 99%
“…Scleral remodeling is known to be closely related to myopia development [ 35 , 36 ]. Studies have shown that phosphorylation of ERK1/2 leads to the upregulation of MMP-2 transcription and translation, which then regulates ECM degradation and causes scleral remodeling in FDM guinea pigs [ 49 ]. It was recently reported that ADCY1 activation stimulates ERK phosphorylation [ 48 , 62 ].…”
Section: Discussionmentioning
confidence: 99%
“…In the present study, it was observed that the VEGFA content in the tears of highly myopic patients was signi cantly lower than that of patients in the EM group. Although it is still controversial whether the VEGFA content in the tears of myopic patients can accurately re ect the VEGFA levels in intraocular structures, including the retina and choroid, the change in VEGFA levels in the tears in the current study was used to re ect the change in VEGFA expression in the choroid after onset of myopia to some degree 45,46 . To demonstrate that the reduction in choroidal blood ow in patients with high myopia is caused by a decrease in VEGFA expression in the choroid, we replicated the FDM guinea pig model and observed a signi cant decrease in VEGFA expression in the choroid of myopic guinea pigs, and choroidal atmounts also showed a signi cant decrease in the number of choroidal vessels.…”
Section: Discussionmentioning
confidence: 99%
“…According to the literature, we found that Amphiregulin (AREG) is a direct target gene of TAZ (Han, et al 2014;Martini, et al 2017). AREG has been reported to be involved in various physiopathological processes such as cancer (Steponaitis, et al 2019), scleral remodeling (She, et al 2022), skin brosis (Zhang, et al 2021a), bone formation (Raimondo, et al 2019). In cancer, AREG has been validated as an oncogene (Ahn, et al 2013).…”
mentioning
confidence: 99%